2014
DOI: 10.1017/s0031182013002199
|View full text |Cite
|
Sign up to set email alerts
|

Modelling inter-human transmission dynamics of Chagas disease: analysis and application

Abstract: Transmission of Trypanosoma cruzi, the causal agent of Chagas disease, has expanded from rural endemic to urban areas due to migration. This so-called urban Chagas is an emerging health problem in American, European, Australian and Japanese cities. We present a mathematical model to analyse the dynamics of urban Chagas to better understand its epidemiology. The model considers the three clinical stages of the disease and the main routes of inter-human transmission. To overcome the complexities of the infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The importance of HI individuals has also been shown in our previous work in a triatomine-free scenario (Fabrizio et al . 2014 b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of HI individuals has also been shown in our previous work in a triatomine-free scenario (Fabrizio et al . 2014 b ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper (Fabrizio et al . 2014 b ), we presented a model of the so-called urban Chagas , i.e. Chagas disease in a triatomine-free scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In endemic countries, Chagas disease is primarily transmitted by triatomine vectors, predominantly in rural areas. However, human migration and other forms of transmission have changed the epidemiology/epizootiology of Chagas disease, which is currently affecting peri-urban and urban areas ( 5 , 6 ). Other important mechanisms of transmission include blood transfusion, organ transplants, oral ingestion, laboratory accidents, vertical transmission from mother to child, or needle sharing ( 2 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of patients detected by routine screenings of blood banks or organ banks in the USA led to the implementation, in early 2007, of the first diagnostic test for Chagas disease approved by the Food and Drug Administration for use in the USA [ 7 ]. It has been suggested that around 94% of new infections of urban Chagas occur from subjects with the indeterminate or chronic asymptomatic chagasic form (ICF) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%